2022
DOI: 10.3390/children9091312
|View full text |Cite
|
Sign up to set email alerts
|

Relationships between Functional Movement Quality and Sprint and Jump Performance in Female Youth Soccer Athletes of Team China

Abstract: This study aimed to determine the optimal functional movement screen (FMS) cut score for assessing the risk of sport injury, and to investigate the correlations between functional movement quality and sprint and jump performance. Twenty-four (N = 24) athletes performed all tests in one day at 10–30 min intervals, and the FMS test was performed first, without a warm-up session. After a standard warm-up, athletes then completed the Y-balance Test (YBT), sprint, counter-movement jump (CMJ), and standing long jump… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 36 publications
(33 reference statements)
0
1
0
Order By: Relevance
“…According to Cook, issues at the foundational level can impact higher layers of movement capabilities. Previous research has found associations between functional movement and aspects such as physical performance, movement performance ( Fitton Davies et al, 2022 ; Zhang et al, 2022 ), and the occurrence of sports injuries ( Chorba et al, 2010 ; Dïnç & Arslan, 2020 ). However, the relationship between functional movement and movement performance lacks consensus ( Stapleton et al, 2021 ; Bennett et al, 2022 ).…”
Section: Introductionmentioning
confidence: 99%
“…According to Cook, issues at the foundational level can impact higher layers of movement capabilities. Previous research has found associations between functional movement and aspects such as physical performance, movement performance ( Fitton Davies et al, 2022 ; Zhang et al, 2022 ), and the occurrence of sports injuries ( Chorba et al, 2010 ; Dïnç & Arslan, 2020 ). However, the relationship between functional movement and movement performance lacks consensus ( Stapleton et al, 2021 ; Bennett et al, 2022 ).…”
Section: Introductionmentioning
confidence: 99%